Competition in the marketing of petroleum products in Nigeria - Fawibe, Reuben Oladiran (Ibadan : University of Ibadan, 1971)
This book is a thesis conducted by s student from the University of Ibadan, in fulfilment of the requirement for the M.Sc. Degree in Economics University of Ibadan. The study seek to analyze the nature and extent of competition in the marketing of petroleum products in Nigeria.
Includes bibliographical references: p. 167-171.
hza 01/02/2019
Ref
Keywords: Petroleum industry; Nigeria